(untitled) (Education in the 21st Century, 2023)
Today, in the 21st century, higher education has become one of the main factors in the formation of the economy, ensuring the reproduction of human capital - the most important resource for the development of society. This article examines the higher education systems of the Republic of Armenia and Italy, and also conducts a comparative analysis in order to identify the features of managing the higher education systems of the two countries. In particular, the article presents the structure of higher education systems in Armenia and Italy, the features of management of vocational educational institutions, and also conducts a comparative analysis. The results of the comprehensive study are presented in the form of tables, from which the similarities and differences in the management of the higher education systems of the two countries become apparent.